Pengaruh Motif Aplikasi Line Webtoon terhadap Kepuasan Khalayak Membaca Komik Digital - Lina Fardiana Wulandari Faisal; Zulfebriges (Bandung Conference Series: Communication Management, 2022)
Abstract. Technological advances are running very fast today and play an important role in communication practices. Comics were originally in the form of print media in the form of books. Comics are now starting to change in electronic form and are distributed over the internet. In using the Line Webtoon application, each user has a certain motive to fulfill their satisfaction or needs. The study, entitled "The Effect of Motives for Using Line Webtoon Applications on Audience Satisfaction Reading Digital Comics" aims to determine how much influence the motives for using Line Webtoon applications have on the satisfaction of digital audiences in reading komaca comics. This study uses quantitative research methods, with a quantitative descriptive approach. Data collection techniques using questionnaires and literature study. This research uses new media theory. The results of this study based on the results of hypothesis testing indicate that the value of sig. - all hypotheses has a value below 0.05, then Ho is rejected and Ha is accepted, from these results the hypothesis has a significant effect. This study illustrates that audience satisfaction in reading digital comics is based on their motives for using the Line Webtoon application. Abstrak. Kemajuan teknologi berjalan dengan sangat cepat saat ini dan berperan penting dalam praktik komunikasi. Komik pada awalnya berupa media cetak dalam bentuk buku. Komik kini mulai berubah dalam bentuk elektronik dan didistribusikan melalui internet. Dalam penggunaan aplikasi Line Webtoon ini, setiap penggunanya memiliki motif tertentu untuk memenuhi kepuasan atau kebutuhannya. Penelitian yang berjudul “Pengaruh Motif Penggunaan Aplikasi Line Webtoon terhadap Kepuasan Khalayak Membaca Komik Digital” bertujuan untuk mengetahui seberapa besar pengaruh antara motif penggunaan aplikasi Line Webtoon terhadap kepuasan khalayak membaca komik digital. Penelitian ini menggunakan metode penelitian kuantitatif, dengan pendekatan deskriptif kuantitatif. Teknik pengumpulan data menggunakan kuesioner dan studi pustaka. Penelitian ini menggunakan teori new media. Hasil penelitian ini berdasarkan hasil uji hipotesis menunjukkan bahwa nilai sig.- semua hipotesis memiliki nilai dibawah 0,05 maka Ho ditolak dan Ha diterima, dari hasil tersebut hipotesis berpengaruh signifikan. Penelitian ini menggambarkan bahwa kepuasan khalyak dalam membaca komik digital ini didasari oleh bagaimana motif mereka dalam menggunakan aplikasi Line Webtoon.